2018
DOI: 10.1097/sap.0000000000001457
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic Unit Boundary Approach to Large Fibroadenoma Resection

Abstract: Concentric circumareolar approach can be used to resect large benign breast tumors while concealing the scar along the aesthetic unit boundary of the breast. The cosmetic outcome and recovery were promising. The approach is simple to execute, highly reproducible, and less dependent on intuition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In addition, Srivastava et al 22 performed a free nipple graft for the excision and reconstruction of a giant fibroadenoma in a 12-year-old female. Concentric circumareolar incisions, performed by Lai et al 24 and Wang et al, 18 and the use of a single circumareolar incision or Swiss-roll technique, performed by Naraynsingh et al 25 and Zeeshan et al, 26 have both been shown to provide satisfactory outcomes for fibroadenoma excision by reducing scarring. Chang et al 3 used McKissock bipedicle technique for breast reconstruction after mass excision to preserve breast parenchyma, adjust the skin envelope, and obtain nipple-areola symmetry.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, Srivastava et al 22 performed a free nipple graft for the excision and reconstruction of a giant fibroadenoma in a 12-year-old female. Concentric circumareolar incisions, performed by Lai et al 24 and Wang et al, 18 and the use of a single circumareolar incision or Swiss-roll technique, performed by Naraynsingh et al 25 and Zeeshan et al, 26 have both been shown to provide satisfactory outcomes for fibroadenoma excision by reducing scarring. Chang et al 3 used McKissock bipedicle technique for breast reconstruction after mass excision to preserve breast parenchyma, adjust the skin envelope, and obtain nipple-areola symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Srivastava et al 22 performed a free nipple graft for the excision and reconstruction of a giant fibroadenoma in a 12-year-old female. Concentric circumareolar incisions, performed by Lai et al 24 and Wang et al, 18 and the use of a single circumareolar incision or Swiss-roll technique, performed by Naraynsingh et al 25 and Zeeshan et al, 26 As in choosing the appropriate breast cancer patient for breast conservation therapy with lumpectomy and oncoplastic breast reduction, patient selection for this technique in the pediatric population is also critical. Perhaps the most important component of patient selection is evaluating and estimating the breast volume that will remain after mass removal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations